2022
DOI: 10.2147/prbm.s350191
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Subjective Happiness: Testing the Importance of Emotional Intelligence Facets Beyond Perceived Stress

Abstract: Emotional intelligence (EI) is typically linked to higher subjective happiness scores in human service professionals. It is unknown which EI facets are more predictive in explaining subjective happiness beyond that accounted for by other key predictors such as perceived stress. This study investigated which EI facets were the most predictive in explaining subjective happiness above perceived stress in a relatively large sample of Spanish teachers. Methods: The sample was composed of 1323 Spanish teaching profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…We found that even socio-emotional competence had an effect on work engagement, as expected (H3). This finding aligns with previous research indicating that individuals with higher socio-emotional competence are more likely to be engaged in their work (Mérida-López et al, 2022), and emphasizes the importance of developing and promoting socio-emotional skills among teachers to enhance their job satisfaction, performance, and overall wellbeing. Previous studies have documented the protective role of socio-emotional competence, especially emotion regulation skills, in reducing the negative effect of stress and anxiety, which are feelings that are frequently experienced in the teaching profession.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that even socio-emotional competence had an effect on work engagement, as expected (H3). This finding aligns with previous research indicating that individuals with higher socio-emotional competence are more likely to be engaged in their work (Mérida-López et al, 2022), and emphasizes the importance of developing and promoting socio-emotional skills among teachers to enhance their job satisfaction, performance, and overall wellbeing. Previous studies have documented the protective role of socio-emotional competence, especially emotion regulation skills, in reducing the negative effect of stress and anxiety, which are feelings that are frequently experienced in the teaching profession.…”
Section: Discussionsupporting
confidence: 90%
“…Teachers' social and emotional competence can be an important factor in preventing burnout and fostering a positive attitude toward their work (Montgomery and Rupp, 2005;Mérida-López et al, 2022). The ability to control one's emotions, one's empathy, one's capacity to form positive connections, and ability to manage positive and negative conflict effectively are all examples of social and emotional competences.…”
Section: The Protective Role Of Teachers' Socio-emotional Competencementioning
confidence: 99%
“…(Tuyakova et al, n.d.), -Trait Meta-Mood Scale‖, the -Spanish Burnout Inventory‖ and -Psychological Well-Being Scales‖, (Lucas-Mangas et al, 2022). Some other scales used to measure are -Wong and Law Emotional Intelligence Scale‖, the -Subjective Happiness Scale‖, and the -Perceived Stress Scale‖ (Mérida-López et al, 2022). Till date, a very significant gap is visible on cross-dimensional research covering EI , especially while measuring impact and performance of EI (Algozhina et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alongside ability models and trait models are the so-called mixed models, which define emotional intelligence as a set of cognitive abilities, emotional competencies, and stable personality traits [16]. Several studies have shown a positive relationship between self-perceived emotional intelligence and personal well-being, both in its cognitive and affective components [17][18][19][20][21][22][23][24]. Likewise, meta-analytic studies have also shown a positive relationship between emotional intelligence and subjective well-being in various populations [25][26][27].…”
Section: Introductionmentioning
confidence: 99%